Single application of 0.8% hyaluronic acid as a coadjuvant of nonsurgical treatment in nonsmoking patients with periodontitis: A split-mouth, randomized, controlled pilot clinical trial - Joana Cristina Rico Farto Lobato; Mafalda Alexandra dos Santos Vilhena; Catarina Izidoro; Ricardo Castro Alves; Luís Proença (Wolters Kluwer Medknow Publications, 2019)
Background: Topical coadjuvants might be indicated to increase the results of nonsurgical periodontal treatment and overcome some of its limitations. The aim of this study was to evaluate the clinical benefits of a single topical application of 0.8% hyaluronic acid (HA) as a coadjuvant to scaling and root planing (SRP) in periodontal patients. Materials and Methods: Sixteen patients diagnosed with periodontitis were recruited to participate in this split-mouth randomized controlled trial. At baseline, oral hygiene instructions, prophylaxis, and SRP were performed in both sides; additionally, a subgingival application of HA at 0.8% was made in the test side. Several clinical parameters were assessed at baseline, 6, and 12 weeks later: full mouth plaque score, gingival score, bleeding on probing (BoP), probing depth (PD), and clinical attachment level (CAL). Results: At the end of 12 weeks, there was a overall improvement in all periodontal parameters in both sides (P < 0.05). Test sides showed less BoP when compared to the control sides (9.4 ± 4.0 vs. 14.9 ± 8.9, P < 0.05). Other periodontal parameters such as PD and CAL showed a slight improvement in comparison with the control sides, but the difference was not statistically significant (P > 0.05). Conclusion: Results from this study indicate that a single subgingival application of 0.8% HA seems to reduce gingival inflammation and improve clinical parameters, particularly BoP. Further studies are needed to evaluate the effect of repeated application of HA and long-term results.